Mediation effects of engagement and job satisfaction between Herzberg’s theory and performance: with moderation role of abusive supervision - Md. Abu Issa Gazi; Abdullah Al Masud; Md. Emon; Mohammad Bin Amin; Amani AbdAlatti; Sukanta Biswas; Abdul Rahman bin S Senathirajah; Veronika Fenyves (Cogent Business & Management, 2025)
The purpose of our research is to examine the dual mediation effect of job satisfaction and engagement on the association between job performance and hygiene parameters. These mediators were selected for capturing the varied routes by which hygiene factors affect job performance, as engagement and satisfaction represent distinct components of employee well-being. Additionally, this study investigates how abusive supervision moderates job engagement and job satisfaction on job performance, which may lessen the benefits of good work circumstances on performance. A quantitative study method is employed by surveying 410 Bangladeshi workers in the government, semi-government and private sectors. Structural equation modeling is utilized to analyze the data in order to look for correlations and moderating effects. The findings indicate that hygiene factors have a significant positive effect on job engagement and satisfaction, which improves performance. Nevertheless, these effects are weakened by abusive supervision because employees under such authority exhibit lower performance even when they are highly engaged with their work and satisfied with it. This study expands on Herzberg’s Two-factor Theory for examining abusive supervision as a moderating component. It illustrates how poor supervisory behaviors can negate the positive influence of job engagement and satisfaction on performance. The research stresses the need for supportive supervisory practices so as to improve employee productivity.